SEDIMEN LARUT DALAM ASAM DAN TIDAK LARUT DALAM ASAM DI PERAIRAN TELUK BUYAT DAN SEKITARNYA - Manengkey, Hermanto WK (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
Information on water conditions, such as sedimentation, physical factors, and coral reef ecosystem, needs to be understood that the stakeholders could optimally utilize the the area. This study was aimed at determining the sediment content of Buyat Bay and its surroundings dissolved and undissolved in the acid solution. Results found that the terrestrial sediments (Lithogenous) were not soluble in the acid solution and the marine ones (Biogenous) were soluble.